Analysis of the Marketing Creativity Training Program in the Digital Era - Dicky Jhon Anderson Butarbutar; Diding Kusnady; Maikel Rudianto; Irma Hariyanti Siregar; Donny Dharmawan (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
The goals of marketing in the digital era are to reach a wider audience with precision, build brand awareness, increase conversions and sales, build strong customer relationships through direct interactions, accurately measure campaign results, and improve cost efficiency by leveraging digital platforms such as social media, search engines, and email to promote products or services. The purpose of this study was to understand analysis of the marketing creativity training program in the digital era. This research was analyzed using a descriptive analysis approach. To assist in the presentation of this descriptive analysis approach, secondary data is required in the form of books containing theories and other sources, such as journals and media articles. The results of this study provide insight into the need to analyze the marketing creativity training program in the digital era, as they demonstrate an impact on improving sales performance and business competitiveness. An effective the marketing creativity training program in the digital era equips participants with core competencies in digital media mastery and the ability to adapt to market trends. An effective the marketing creativity training program in the digital era is achieved through mastery of digital platforms, creative content development, digital data analysis, and adaptation and innovation.